Tax Law And Its Implementation For The Welfare Of The People - Armeni, Sinta Bela; Hanila , Siti; Nasution , Suswati; Zoniarti , Zoniarti (Utami Publisher, 2025)
Taxes are one of the economic tools of a country. As a source of national income, some taxes account for more than 50% of national income. For example, if a country has higher taxes, more jobs can be created, unemployment rate decreases, and good education and health care can be achieved. They are also a good tool for income distribution. At the same time, income distribution is also the biggest problem in the current economy. The rich get richer and the poor get poorer. When taxes are used as a tool to reduce income imbalance, this paper will explain whether this affects people's well-being.